Classical Victorians : scholars, scoundrels and generals in pursuit of antiquity - Richardson, Edmund, 1982- (Classics after antiquity, 2013)
"Victorian Britain set out to make the ancient world its own. This is the story of how it failed. It is the story of the headmaster who bludgeoned his wife to death, then calmly sat down to his Latin. It is the story of the embittered classical prodigy who turned to gin and opium - and the virtuoso forger who fooled the greatest scholars of the age. It is a history of hope: a general who longed to be an Homeric hero, a bankrupt poet who longed to start a revolution. Victorian classicism was defined by hope - but shaped by uncertainty. Packed with forgotten characters and texts, with the roar of the burlesque-stage and the mud of the battlefield, this book offers a rich insight into nineteenth-century culture and society. It explores just how difficult it is to stake a claim on the past"--